Suporte social: adaptação transcultural do Social Support Appraisals e desenvolvimento socioemocional de crianças e adolescentes - Squassoni, Carolina Elisabeth (2009)
The association between social support and positive results in health has been increasingly highlighted in the literature and social support has been seen as a protective factor to child development. However, most research involving social support and outcomes of health and development of children and adolescents has focused on the indirect influence of social support of parents in the development of children. The aim of this study was to identify possible correlations between the perceived social support for children and adolescents at situation of personal and social risk and their social and emotional development and as specific goals: a) the cross cultural adaptation of Brazil of the scale SOCIAL SUPPORT APPRAISALS, and b) identify associations of some variables on the perception of social support of children and adolescents on the self-assessment the child with regard to their development and the parents evaluation of socioemocional development of their children. To achieve the proposed objectives were carried out two studies. The Study 1 involved a crosscultural adaptation of the Portuguese version of the SOCIAL SUPPORT APPRAISALS and the Study 2 answered by the study of correlation. Were participants of Study 1, 218 children and adolescents and 10 graduated professionals. We performed the following analysis: Cronbach's Alpha, Factor Analysis and Analysis of Variance. The results pointed to an index of internal consistency to the general scale of 0,74, the factor analysis confirmed the proposed structure with four factors (family, friends, teachers and others), by analysis of variance were found significant differences in the perception of social support of according to grade and gender and age and grade of participants. In the Study 2 participated 51 children and adolescents aged between 11 and 13 years and their parents. Children and adolescents were linked to non-governmental institutions that provide support services to children and adolescents in situations of personal and social risk. Instruments used to collect data were the Brazilian version of the SOCIAL SUPPORT APPRAISALS, the Strengths and Difficulties Questionnaire, the Questionnaire for Identification and Characterization of the Child and the Criterion of Economic Classification Brazil. Tests were carried out on the Pearson correlation analysis of the Pearson correlation, Analysis of variance and Analysis Group. The results indicated that the higher the perceived of total social support, less the symptoms of problems presented by children and adolescents, in addition to that there were other variables associated with results of mental health and level of social support of the participants, such as school repetition, the degree of parental education, among others.